MENINGKATKAN HASIL BELAJAR FISIKA SISWA MELALUI PEMBERIAN SOAL TES BERGAMBAR PADA SISWA SMA - Maria.S, Haratua Tiur (Universitas Tanjungpura, 2013)
This research is aimed to investigate the influence of implementing physic?s test questions with picture to senior high school students for the increasing of physic students? learning outcome. Research is done in four different schools from different regencies in west Borneo by using data collection tools in form of analytical test to the students grade XI. The research is done by comparing the students? test result who has given the analytical test (verbal representation) and analytical test with picture (verbal representation and picture). Research outcome shows that most of the student learning outcome who has given the test question with picture is higher (11.57) rather than student learning outcome who has given the test question without picture (9.89) . Keywords: Learning outcome, physic, test question with picture